Absorptive capacity of the Egyptian economy : an examination of problems and prospects - Ahmad, Yusuf J. (Paris : Organisation for Economic Co-operation and Development, 1976)
The study among others attempts to provide a perspective in which the flow of financial resources to the Egyptian economy could be examined. It is in that sense an exercise in the determination of the indirect absorptive capacity generated by surplus oil revenues during 1974 and the first quarter of 1975.
Includes bibliographical references: p. 181-182.
rpm 13/11/2017
Loans
Keywords: Absorptive capacity (Economics); Egypt